Refractory ulcerative proctitis: How to treat it?. (February 2018) - Pineton de Chambrun, Guillaume; Tassy, Barbara; Kollen, Laura; Dufour, Gaspard; Valats, Jean-Christophe; Bismuth, Michael; Funakoshi, Natalie; Panaro, Fabrizio; Blanc, Pierre
Abstract: Ulcerative proctitis is defined as a mucosal inflammation limited to the rectum. Ulcerative proctitis is responsible for distressing symptoms and alteration of patient quality of life. Effective treatment is important to prevent or delay proximal extension of the disease and to improve quality of life. Refractory ulcerative proctitis is defined as the failure of topical and oral 5-aminosalicylic acid and corticosteroids. Medical management of refractory ulcerative proctitis may be challenging as there is little evidence regarding drug efficacy in this clinical situation. Data are currently available for azathioprine, topical tacrolimus and anti -TNF monoclonal antibodies as rescue treatment for refractory ulcerative proctitis. Other biologics may be of benefit despite a lack of dedicated clinical trials. Ultimately, experimental therapies such as epidermal growth factor enemas, appendectomy or fecal transplantation may be tried before restorative proctocolectomy with J pouch anastomosis, which has demonstrated good results with regards to clinical remission and quality of life.